Heat-Treated Bifidobacterium longum CECT-7347: A Whole-Cell Postbiotic with Antioxidant, Anti-Inflammatory, and Gut-Barrier Protection Properties - Patricia Martorell; Beatriz Alvarez; Silvia Llopis; Veronica Navarro; Pepa Ortiz; Nuria Gonzalez; Ferrán Balaguer; Antonia Rojas; Empar Chenoll; Daniel Ramón; Marta Tortajada (MDPI AG, 2021)
Non-viable preparations of probiotics, as whole-cell postbiotics, attract increasing interest because of their intrinsic technological stability, and their functional properties, such as immune system modulation, gut barrier maintenance, and protection against pathogens. However, reports on Bifidobacteria-derived postbiotics remain scarce. This study aims to demonstrate the functional properties of a heat-treated (HT), non-viable, Bifidobacterium longum strain, CECT-7347, a strain previously selected for its anti-inflammatory phenotype and ability to improve biomarkers of intestinal integrity in clinical trials. The study used the nematode Caenorhabditis elegans and HT-29 cell cultures as eukaryotic model systems. Our results show that HT-CECT-7347 preserves the capacity to protect against oxidative stress damage, while it also reduces acute inflammatory response and gut-barrier disruption, and inhibits bacterial colonization, by activating pathways related to innate immune function. These findings highlight the interest of the ingredient as a novel postbiotic and pave the way to broaden the range of HT-CECT-7347 applications in gut health.